(untitled) (Research, Society and Development, 2022)
Bacteriophages (phages) are viruses which infect prokaryotes, their applicability and recognition as a mechanism against bacterial species are getting importance in the medical science. The present study aimed to recognize genes related to bacteriophages in samples of Enterobacter aerogenes, as a possible resource for controlling this pathogen. The used genome belonged to an E. aerogenes infection isolated from the Intensive Care Unit of a Public Hospital in Recife-PE and submitted to genomic sequencing. After prediction and gene annotation, there was the identification of two genes related to bacteriophages, through manual and precise analysis and comparison with the genes of the colonization isolated. Regarding the results obtained, several genes were found in the infection isolated (chromosomal and plasmid DNA) with important properties. When compared with the genes of the colonization isolated, it was possible to observe a proximity and similarity between them, differing in only one single and exclusive gene in the chromosomal DNA from infection isolated. Therefore, it was possible to show a variety of genes related to bacteriophages in the analyzed isolated, which exposes the importance of phage therapy as an alternative to control pathogenic bacteria.